2010
DOI: 10.1007/s10118-010-1021-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic hydrogels as scaffolds for manipulating endothelium cell behaviors

Abstract: Synthetic hydrogels can be used as scaffolds that not only favor endothelial cells (ECs) proliferation but also manipulate the behaviors and functions of the ECs. In this review paper, the effect of chemical structure, Young's modulus (E) and zeta potential (ζ ) of synthetic hydrogel scaffolds on static cell behaviors, including cell morphology, proliferation, cytoskeleton structure and focal adhesion, and on dynamic cell behaviors, including migration velocity and morphology oscillation, as well as on EC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…1,2 Since the pioneering work of Wichterle and Lim 3 in 1960 on covalently crosslinked polyhydroxyethylmethacrylate hydrogels, synthetic hydrogels have been thought to have great potential for use in articial implants, biomedical devices, tissue engineering and regenerative medicine as a result of the similarity of their soness and water content to natural so tissues, their high permeability for water-soluble nutrients and metabolites, and their potential biocompatibility. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, the actual utilization of classic hydrogels has been seriously impeded by their poor mechanical properties. To solve this problem, several types of chemical hydrogels with high mechanical strength have been developed over the last few decades, including covalently crosslinked sliding hydrogels, 17 double-network hydrogels, 18,19 macromolecular microsphere composite hydrogels, 20 tetra-poly(ethylene glycol) PEG hydrogels, 21 covalent bond and hydrogen bond crosslinked hydrogels, 22 inorganic clay crosslinked nanocomposite hydrogels, 23 and polyacrylamide-alginate hybrid hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since the pioneering work of Wichterle and Lim 3 in 1960 on covalently crosslinked polyhydroxyethylmethacrylate hydrogels, synthetic hydrogels have been thought to have great potential for use in articial implants, biomedical devices, tissue engineering and regenerative medicine as a result of the similarity of their soness and water content to natural so tissues, their high permeability for water-soluble nutrients and metabolites, and their potential biocompatibility. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, the actual utilization of classic hydrogels has been seriously impeded by their poor mechanical properties. To solve this problem, several types of chemical hydrogels with high mechanical strength have been developed over the last few decades, including covalently crosslinked sliding hydrogels, 17 double-network hydrogels, 18,19 macromolecular microsphere composite hydrogels, 20 tetra-poly(ethylene glycol) PEG hydrogels, 21 covalent bond and hydrogen bond crosslinked hydrogels, 22 inorganic clay crosslinked nanocomposite hydrogels, 23 and polyacrylamide-alginate hybrid hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Most hydrogels, whether covalently or non-covalently cross-linked, are mechanically weak and exhibit poor elasticity and a lack of physiochemical functions4. Pioneering double network hydrogels can achieve certain mechanical requirements using a typical two-step polymerization56. A nanocomposite (NC) hydrogel is another original material that can achieve ultrahigh mechanical properties due to the multiple non-covalent effects between clay nanosheets (Clay-NS) and polyacrylamide chains78910.…”
mentioning
confidence: 99%
“…These results are consistent with our recent study (Yang JJ, Liu JF, Kurokawa T, Gong JP; unpublished) that demonstrated the self‐renewal behaviour of miPS cells on hydrogels regardless of changes in elasticity. In our previous studies, we found that the elasticity of hydrogels plays different roles on cell behaviour of anchorage‐dependent and ‐independent cells (Yang et al ., , ; Chen et al ., ). The behaviours of anchorage‐dependent cells such as endothelial cells were regulated by the elasticity of hydrogels.…”
Section: Discussionmentioning
confidence: 97%